(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: The high resistance attributed to biofilms can result in recurrence and persistence of infections with attendant consequences of increased morbidity and mortality rates, increased cost of treatment as well as length of hospital stay of the patient. Objectives: This study aimed at examining the biofilm-forming capacity of bacterial isolates from the external body of cockroaches (Periplaneta americana) and their susceptibility to selected commonly used antibiotics. Methods: Bacterial isolates associated with seventy (70) cockroaches were isolated, identified and characterized using morphology and conventional biochemical tests. The biofilm-forming capacity of the isolates was evaluated using the Congo red agar (CRA) method. The antibiotic susceptibility profiles of the CRA-positive isolates to selected commonly used antibiotics were evaluated using the Kirby-Bauer disc diffusion method. Results: Of the one hundred and four (104) isolates, Bacillus subtilis was the predominant bacterial species (77.9%) while the least was Salmonella typhi (1.0%). However, 42% of the isolates showed tendency to form biofilms. The susceptibility study revealed that gentamicin was active against both Gram-positive and negative biofilm-formers. Conclusion: This study concluded that cockroaches (Periplaneta americana) can habour some bacterial species capable of forming biofilms which may adversely affect public health.